2008
DOI: 10.1093/aje/kwn028
|View full text |Cite
|
Sign up to set email alerts
|

Incident Diabetes and Pesticide Exposure among Licensed Pesticide Applicators: Agricultural Health Study, 1993-2003

Abstract: Exposure to certain environmental toxicants may be associated with increased risk of developing diabetes. The authors' aim was to investigate the relation between lifetime exposure to specific agricultural pesticides and diabetes incidence among pesticide applicators. The study included 33,457 licensed applicators, predominantly non-Hispanic White males, enrolled in the Agricultural Health Study. Incident diabetes was self-reported in a 5-year follow-up interview (1999-2003), giving 1,176 diabetics and 30,611 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
190
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(205 citation statements)
references
References 29 publications
8
190
4
3
Order By: Relevance
“…Furthermore, the diabetogenic effects of POPs have been shown to be much stronger in persons with higher BMIs than those with lower BMIs [29][30][31]. As such, obesity is regarded as a significant modifying factor for the association between OC pesticides and type 2 diabetes [31,32]. The results of this study indicate that obesity contributes to an increased body burden of OC compounds and thereby contributes, at least in part, to pathogenesis of PAD.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, the diabetogenic effects of POPs have been shown to be much stronger in persons with higher BMIs than those with lower BMIs [29][30][31]. As such, obesity is regarded as a significant modifying factor for the association between OC pesticides and type 2 diabetes [31,32]. The results of this study indicate that obesity contributes to an increased body burden of OC compounds and thereby contributes, at least in part, to pathogenesis of PAD.…”
Section: Discussionmentioning
confidence: 67%
“…Pelletier et al found that obese individuals were associated with higher levels of circulating OCs, whereas both leaner sedentary individuals and athletes had lower levels of these compounds [28]. Furthermore, the diabetogenic effects of POPs have been shown to be much stronger in persons with higher BMIs than those with lower BMIs [29][30][31]. As such, obesity is regarded as a significant modifying factor for the association between OC pesticides and type 2 diabetes [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This trend cannot be explained completely by dietary, social and behavioral changes that have occurred during the same time (Biro and Wien, 2010). Simultaneously, emerging evidence suggests that persistent organic pollutants, including insecticides, are positively linked to altered glucose homeostasis (Boada et al, 2007;Montgomery et al, 2008;Son et al, 2010;Rezg et al, 2010;Lee et al, 2011). There is currently limited knowledge on the underlying biochemical mechanisms by which insecticides alter glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent findings from this prospective study of nearly 32,000 individuals showed that lifetime cumulative exposure to seven specific chlorinated pesticides increased the likelihood of diabetes (Montgomery et al 2008). It is recognized that the disease is multifactorial with a complex interplay between biology, the environment, lifestyles and health while limited research has examined occupational factors that contribute to the risk of diabetes, there is evidence of an association with environmental exposure to pesticides.…”
Section: Epidemiologic Trends In Diabetesmentioning
confidence: 99%